HUBUNGAN PENGETAHUAN PERAWAT TENTANG PEMBERIAN LABEL TRIASE DENGAN TINDAKAN PERAWAT BERDASARKAN LABEL TRIASE DI IGD RUMAH SAKIT PETROKIMIA GRESIK - Erna Dwi Wahyuni; Abu Bakar; Wieji Santosa (Critical Medical and Surgical Nursing Journal (CMSNJ), 2015)
Introduction: Triage is a selection system and patient selection to determine the level of severity and handle patient priority. There is an error in sorting triage so that should be handled on an out patient poly but it handled in emergency room so that there are patients who need immediate care treatment cannot handled well. The purpose of this study was to analyze the relationship between knowledge about labeling triage and action based on labeling Emergency Room. Methods: This study used descriptive correlation design with cross sectional method. The population was nurse in emergency room at Petrokimia Hospital Gresik. Total sampling was used in this study. The sample in this study were 12 respondents. The independent variable was knowledge about labeling triageand the dependent variable was action based on labeling emergency room. The instrument of this study used questionnaire and observation paper then analyzed using Spearman Rho statistical test with level of significant of p<0.05. Result: The results of this study showed that there was very strong relationship between knowledge about labeling triage and action based on labeling emergency room (p=0.002; r=0.802).Conclusions: From the result of this study were expected the description for nurses that so the influence of knowledge and attitude in handling emergency patients. Nurses were motivated to do better action by increasing knowledge of discussions and continuing formal education.